Disability, education and employment in developing countries : from charity to investment - Lamichhane, Kamal (New Delhi : Cambridge University Press., 2015)
"Revolves around the discussion that human capital such as education and employment are the most important factors for inclusion and economic empowerment of the disabled, and their accessibility not only improves their livelihood, but also brightens the prospects of their poor families, and of the society as a whole"--Provided by publisher.
Fundamentals of disability studies -- Disability and the global employment situation -- Disability and the role of education in jobs : case studies from Nepal and the Philippines -- Disability and jobs in a post-conflict country : Cambodia -- Gender and job comparisons between people with and without disabilities in Bangladesh -- Disability and human capital investment -- Disability and breaking the vicious cycle of poverty : a case study in Nepal -- Disability and job satisfaction differentials -- Disability and determinants of education : a case from India -- Disability and barriers to education -- The way forward : investment in disability.
Includes bibliographical references and index.
Keywords: People with disabilities -- Asia; People with disabilities -- Education -- Asia; People with disabilities -- Employment -- Asia